Outcome of Pelvic Bone Sarcomas in Children. Issue 10 (November 2018) - Laitinen, Minna; Parry, Michael; Albergo, Jose I.; Jeys, Lee; Sumathi, Vaiyapuri; Grimer, Robert
Abstract : Background: Malignant bone tumors of the pelvis in children are rare and knowledge of their behavior is limited. Methods: A total of 113 skeletally immature patients under 16 years of age, comprising 58 females and 55 males were treated between 1983 and 2014. Tumors comprised Ewing's sarcoma (ES) in 88 (77.9%) or osteosarcoma (OS) in 25 (22.1%). Metastases at diagnosis were present in 36 (31.9%). The mean follow-up was 5.2 years (2 to 16). Results: For patients with ES, the overall survival was 37.1% at 5-years and 33.5% at 10-years and 31.7% at 5- and 10-years in patients with OS. Local recurrence occurred in 24 patients with ES (27.3%) and 7 patients with OS (43.7%). Chemotherapy response was a predictor of local recurrence in ES with the lowest incidence seen in those with a good response to chemotherapy treated with a combination of radiotherapy and surgery. In patients with OS, both surgical margin and chemotherapy response influenced local control. Conclusions: Attaining a wide surgical margin should be the aim of treatment for all children with primary bone tumors of the pelvis. In ES, chemotherapy response has a greater influence on disease free and overall survival. Patients who demonstrate a poor response to chemotherapy should be considered for subsequent radiotherapy. Effort should be directed toward identifying nonhistologic methods of assessing chemotherapy response. Level of Evidence: Level IV—retrospective case study.